(untitled) (Jurnal Manajemen Bisnis, 2024)
The Certified Work Training Program (CWTP) by Dinas Tenaga Kerja Kota Bandung aims to address unemployment challenges in Bandung. Key gaps include limited post-training support and poor alignment with labor market needs. The study evaluates CWTP using the Kirkpatrick Model, SWOT analysis, TOWS matrix, and Analytical Hierarchy Process (AHP), benchmarking it against global programs like Singapore’s SkillsFuture. Findings show moderate success in skill improvement but limited employability outcomes. Recommendations include mentoring, employer partnerships, and robust evaluation systems to enhance workforce sustainability and ensure alignment with market demands, contributing to long-term employment solutions tailored to Bandung’s unique economic context.